Cross cultural understanding and volunteer tourism : the role of sending organisations in fostering cross-cultural understanding - Furusa, Rutendo (Department of Social Development, 2015)
Volunteer tourism has become a popular phenomenon worldwide and questions have been raised about the work that international volunteers do in Third World countries. Scholars have debated the possibility of a cross-cultural ‘misunderstanding’ developing between international volunteers and local community members. This research is based on the idea that there can be a possibility for cross-cultural understanding to take place. This thesis aims to gain better insight into the role that volunteer tourism organisations (VTOs) play in fostering cross-cultural understanding between the volunteers and the local community members that they work with. A framework suggested by tourism expert Eliza Raymond (2007) was used to assess how exactly organisations play a part in encouraging this type of understanding. The research focuses on two VTOs, Projects Abroad and Coaching for Hope as case studies. Both these organisations are involved in the facilitation of development programmes in disadvantaged communities in Cape Town.